(untitled) (Clinics, 2013)
OBJECTIVE: Chemoreceptors play an important role in the autonomic modulation of circulatory and ventilatory responses to changes in arterial O2 and/or CO2. However, studies evaluating hemodynamic responses to hypoxia and hypercapnia in rats have shown inconsistent results. Our aim was to evaluate hemodynamic and respiratory responses to different levels of hypoxia and hypercapnia in conscious intact or carotid body-denervated rats. METHODS: Male Wistar rats were submitted to bilateral ligature of carotid body arteries (or sham-operation) and received catheters into the left femoral artery and vein. After two days, each animal was placed into a plethysmographic chamber and, after baseline measurements of respiratory parameters and arterial pressure, each animal was subjected to three levels of hypoxia (15, 10 and 6% O2) and hypercapnia (10% CO2). RESULTS: The results indicated that 15% O2 decreased the mean arterial pressure and increased the heart rate (HR) in both intact (n = 8) and carotid body-denervated (n = 7) rats. In contrast, 10% O2did not change the mean arterial pressure but still increased the HR in intact rats, and it decreased the mean arterial pressure and increased the heart rate in carotid body-denervated rats. Furthermore, 6% O2 increased the mean arterial pressure and decreased the HR in intact rats, but it decreased the mean arterial pressure and did not change the HR in carotid body-denervated rats. The 3 levels of hypoxia increased pulmonary ventilation in both groups, with attenuated responses in carotid body-denervated rats. Hypercapnia with 10% CO2 increased the mean arterial pressure and decreased HR similarly in both groups. Hypercapnia also increased pulmonary ventilation in both groups to the same extent. CONCLUSION: This study demonstrates that the hemodynamic and ventilatory responses varied according to the level of hypoxia. Nevertheless, the hemodynamic and ventilatory responses to hypercapnia did not depend on the activation of the peripheral carotid chemoreceptors.